Changing labour market participation since the Great Recession: A regional perspective - Calista Cheung; Dmitry Granovsky; Gabriella Velasco (Bank of Canada, 2015)
This paper discusses broad trends in labour force participation and part-time employment across different age groups since the Great Recession and uses provincial data to identify changes related to population aging, cyclical effects and other factors. The main population age groups examined are youth (aged 15-24), prime age (25-54) and older (55 and above). Six main findings are reported. First, aging has been the most important driver of reduced participation. On their own, aging effects would have depressed participation rates by more than they fell between 2007 and 2014, and have been partly offset by rising participation rates of older workers. Second, shifting age composition has had the largest impact on the Atlantic provinces, owing primarily to their shrinking prime-age populations as some workers have migrated west. Third, a considerable part of the overall participation rate decline since 2007 reflects a greater share of prime-age and youth populations that are out of the labour force for various reasons including school, illness, and family responsibilities. These changes appear to be driven by both structural and cyclical forces, although the relative importance of each is unclear. Fourth, effects associated with 'discouraged workers' have been negligible. Fifth, youth participation rates have fallen the most, by 2.8 percentage points since 2007, with 9 per cent of the decline reflecting purely higher school enrolment rates. Sixth, weak business conditions appear to be the main driver behind the shift toward part-time employment since the Great Recession, with involuntary part-time work explaining almost the entire increase since 2007. – – L'étude propose une analyse des grandes tendances que connaissent le taux d'activité et l'emploi à temps partiel chez les différents groupes d'âge depuis le début de la Grande Récession et distingue, à partir de données provinciales, l'influence du vieillissement démographique, d'effets cycliques et d'autres facteurs dans ces évolutions. Les jeunes (15-24 ans), les travailleurs dans la force de l'âge (25-54 ans) et les travailleurs âgés (55 ans et plus) forment les principaux groupes d'âge examinés. Six constats sont décrits. 1) Le vieillissement a été le facteur le plus important dans le recul du taux d'activité. À lui seul, il aurait induit une baisse plus prononcée du taux d'activité que celle enregistrée de 2007 à 2014 si la progression du taux d'activité chez les travailleurs âgés n'avait pas en partie neutralisé cet effet. 2) C'est dans les provinces de l'Atlantique que la modification de la composition des groupes d'âge a les conséquences les plus marquées, qui s'expliquent surtout par la perte de travailleurs dans la force de l'âge au profit des provinces de l'Ouest. 3) Une part considérable du recul global du taux d'activité observé depuis 2007 est attribuable à la présence d'un nombre accru de 25-54 ans et de 15-24 ans hors des rangs de la population active pour des raisons diverses : études, maladie, charges familiales, etc. Seraient en cause des facteurs structurels et cycliques dont l'importance respective est toutefois difficile à discerner. 4) L'incidence des chercheurs d'emploi découragés a été négligeable. 5) C'est chez les jeunes que le taux d'activité a le plus diminué depuis 2007 (- 2,8 points de pourcentage), et une partie de ce repli (9 %) est imputable à la hausse du taux de fréquentation scolaire dans ce groupe d'âge. 6) La piètre situation économique semble justifier le mieux le glissement vers l'emploi à temps partiel qui s'observe depuis le début de la Grande Récession, le travail à temps partiel involontaire expliquant quasi entièrement l'augmentation de l'emploi à temps partiel depuis 2007.
Keywords: E24; E32; J1; J21; J6; 330; Labour markets; Recent economic and financial developments; Regional economic developments; Marchés du travail; Évolution économique et financière récente; Évolution économique régionale